Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/ndr2.12033
|View full text |Cite
|
Sign up to set email alerts
|

First report of lettuce yellowing disease caused by a ‘Candidatus Phytoplasma asteris’‐related strain in Lactuca sativa in Turkey

Abstract: Lettuce (Lactuca sativa) is grown in greenhouse or field conditions in most parts of Turkey. It is generally cultivated as a winter crop in southern regions of Turkey where the climatic conditions are suitable.Commercially grown lettuce showing typical phytoplasma symptoms of yellowing, malformation, little leaf, shoot tip necrosis, stunting and aThis is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…Previously reported causal agent including symptoms such as yellowing, small leaf, necrosis, stunting, and a general decline in lettuce plants had been related to Ca. Phytoplasma asteris through PCR tests (Akkurak et al, 2021). In this study, healthy control (n=6) and symptomatic (n=8) leaves of L. sativa were collected for DNA extraction to confirm our previous findings if the symptomatic lettuce plants still possess the confirmed phytoplasma agent.…”
Section: Plant Materialssupporting
confidence: 55%
See 3 more Smart Citations
“…Previously reported causal agent including symptoms such as yellowing, small leaf, necrosis, stunting, and a general decline in lettuce plants had been related to Ca. Phytoplasma asteris through PCR tests (Akkurak et al, 2021). In this study, healthy control (n=6) and symptomatic (n=8) leaves of L. sativa were collected for DNA extraction to confirm our previous findings if the symptomatic lettuce plants still possess the confirmed phytoplasma agent.…”
Section: Plant Materialssupporting
confidence: 55%
“…In addition to these factors, phytoplasmas, could also be counted as bacterial agents, leading to symptoms such as yellowing, wilting, chlorotic local lesion, deformity, witches' broom formation and stunting in lettuce plants (Akkurak et al, 2021). Phytoplasmas are located in the Mollicute class of the Prokaryotae kingdom.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Akkurak et al. (2021) reported that a phytoplasma causing yellowing symptoms in lettuce in the Turkish province of Sanliurfa belonged to the 16SrI‐B subgroup. Caglayan et al.…”
Section: Figurementioning
confidence: 99%